Fabrication of Circularly Polarized MR‐TADF Emitters with Asymmetrical Peripheral‐Lock Enhancing Helical B/N‐Doped Nanographenes - Wu, Xiugang; Huang, Jing‐Wei; Su, Bo‐Kang; Wang, Sai; Yuan, Li; Zheng, Wei‐Qiong; Zhang, Hu; Zheng, You‐Xuan; Zhu, Weiguo; Chou, Pi‐Tai (Advanced materials (Weinheim), 2022)
Circularly polarized thermally activated delayed fluorescence (CP‐TADF) and multiple‐resonance thermally activated delayed fluorescence (MR‐TADF), which exhibit novel circularly polarized luminescence and excellent color fidelity, respectively, have gained immense popularity. In this study, integrated CP‐TADF and MR‐TADF (CPMR‐TADF) are prepared by strategic design and synthesis of asymmetrical peripherally locked enantiomers, which are separated and denoted as (P,P″,P″)‐/(M,M″,M″)‐BN4 and (P,P″,P″)‐/(M,M″,M″)‐BN5 and exhibit TADF and circularly polarized light (CPL) properties. As the entire molecular frame participates in the frontier molecular orbitals, the resulting helical chirality of (+)/(−)‐BN4‐ and (+)/(−)‐BN5‐based solution‐processed organic light‐emitting diodes (OLEDs) helps in achieving a narrow full width at half maximum (FWHM) of 49/49 and 48/48 nm and a high maximum external quantum efficiency (EQE) of 20.6%/19.0% and 22.0%/26.5%, respectively. Importantly, unambiguous circularly polarized electroluminescence signals with dissymmetry factors (gEL) of +3.7 × 10−3/−3.1 × 10−3 (BN4) and +1.9 × 10−3/−1.6 × 10−3 (BN5) are obtained. The results indicate successful exploitation of CPMR‐TADF‐emitter‐based OLEDs to exhibit three characteristics: high efficiency, color purity, and circularly polarized light. Circularly polarized thermally activated delayed fluorescence (CP‐TADF) and multiple‐resonance thermally activated delayed fluorescence (MR‐TADF) properties are integrated into a new advanced material, a CPMR‐TADF material. OLEDs based on these CPMR‐TADF emitters show excellent performance, attaining a three‐in‐one advantage: high efficiency, color purity, and circular polarized light simultaneously.